S29 Immunological response to airway Aspergillus in CF is reduced following treatment with the CFTR modulator elexacafor-tezacaftor-ivacaftor. (11th November 2022) - Goldsmith, FP; Francis, N; Tewkesbury, D; Barrett, E; Horsley, A; Barry, P
Abstract : Objectives: Aspergillus fumigatus is the most frequently cultured fungal pathogen in sputum from cystic fibrosis (CF) patients. Elexacaftor-tezacaftor-ivacaftor (ETI) is a CFTR modulator which results in significant improvements in lung function. We aimed to investigate the effect of ETI therapy on the serological response to Aspergillus in adult CF patients prescribed ETI. Methods: Data from 275 patients with at least one Phe508del mutation were included. Aspergillus IgG, Aspergillus IgE, total IgE and blood eosinophil count were collected annually 3 years prior to ETI initiation, at baseline (initiation of therapy) and at 3-monthly intervals for the first 12 months of ETI treatment. FEV1 was compared at baseline and at 3 months as a marker of treatment response. Results: There was a significant relative increase in median FEV1 values of 22% at 3 months following ETI initiation (p<0.0001). In the year prior to ETI initiation, there was a significant decrease in total IgE (from 59.3 to 57.5, median change -1.8, p=0.007) and Asp-IgE (from 0.39 to 0.30, median change -0.09, p<0.0001) but not Asp-IgG. In the first 3 months following ETI, there was a significant reduction in all markers (median total IgE 53.6 to 32.9 p<0.001, median Asp-IgE 0.27 to 0.17, p<0.001 and Asp-IgG from 60.0 to 50.5, p<0.001). Asp-IgG continued to decline over the 12 month period post ETI. Asp-IgE however did not change from 3 to 6 months and appeared to increase between 3 and 9 months post ETI. Similarly, total IgE displayed an acute drop but appeared to plateau thereafter. Using suggested clinical ULN for CF, the proportion of patients with significant rises in Asp-IgE declined by 19.1% and Asp-IgG declined by 45%. Conclusions: ETI therapy resulted in an acute, clinically relevant increase in lung function. In the same time frame, we noted an acute reduction in markers of immunological response to Aspergillus fumigatus . This may be due to reduced airway fungal burden, direct effects on immunological response or potentially reduced pathogen exposure as many patients were shielding during the COVID pandemic. Further longitudinal data is required to establish if these changes will be maintained.